Phase I trial of daily subcutaneous SPL-108 injections in combination with paclitaxel in patients with platinum resistant CD44+ advanced ovarian epithelial cancer. Issue 8 (24th June 2022) - Girda, Eugenia; Hou, June; Nelson, David; Finlayson, Malcolm; de Meritens, Alexandre Buckley; Chekmareiva, Marina; Leiser, Aliza; Song, Mihae; Stephenson, Ruth; Chan, Nancy; Tergas, Ana I; Vattakalam, Reena; et al.
Abstract : Objective: Preclinical evidence and early clinical trials have demonstrated the activity of SPL-108, a targeted agent that inhibits CD44 mediated induction of multidrug resistance specifically to paclitaxel and platinum agents. We conducted a phase I, open label, dose escalation study of the safety and tolerability of the combination of SPL-108 with weekly paclitaxel in patients with platinum resistant CD44+ ovarian, primary peritoneal, or fallopian tube cancer. Methods: Patients with platinum resistant histologically proven epithelial ovarian, primary peritoneal, or fallopian tube cancers and measurable disease according to RECIST (Response Evaluation Criteria in Solid Tumours) version 1.1 were selected. Tumors were tested for CD44 expression for eligibility, defined as strong (+++) or moderate (++) staining in ≥20% of the tumor tissue or diffuse + staining. Patients were treated with daily and then twice daily SPL-108 subcutaneous injections and weekly intravenous paclitaxel on days 1, 8, and 15 of a 28 day cycle. Endpoints included safety, determination of maximum tolerated dose, and efficacy. Tumors underwent comprehensive genomic profiling, and cell lines and western blotting were used to study markers of response. Results: We screened 16 patients, and 14 were enrolled based on CD44+ expression. A total of 86% of patients had high grade serous tumors and all had received multiple prior therapies. There were no grade 4–5 toxicities. One patient had grade 3 peripheral sensory neuropathy attributed to paclitaxel and one patient developed presumed colonic perforation attributed to the study drug. No dose reductions or treatment discontinuations were required. All patients tolerated the maximum planned dose; no maximum tolerated dose was reached. Overall response rate was 36%; 5 (36%) patients had partial response and 5 (36%) patients had stable disease. Conclusions: The combination of SPL-108 with weekly paclitaxel was safe and well tolerated. Encouraging antitumor activity was observed, with 72% of patients deriving a clinical benefit. Trial registration: NCT03078400 .